Implications of advanced collision operators for gyrokinetic simulation. (23rd February 2017) - Belli, E A; Candy, J
Abstract: In this work, we explore both the potential improvements and pitfalls that arise when using advanced collision models in gyrokinetic simulations of plasma microinstabilities. Comparisons are made between the simple-but-standard electron Lorentz operator and specific variations of the advanced Sugama operator. The Sugama operator describes multi-species collisions including energy diffusion, momentum and energy conservation terms, and is valid for arbitrary wavelength. We report scans over collision frequency for both low and high k θ ρ s modes, with relevance for multiscale simulations that couple ion and electron scale physics. The influence of the ion–ion collision terms—not retained in the electron Lorentz model—on the damping of zonal flows is also explored. Collision frequency scans for linear and nonlinear simulations of ion-temperature-gradient instabilities including impurity ions are presented. Finally, implications for modeling turbulence in the highly collisional edge are discussed.